PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DI HOTEL DAIMA PADANG - Praci, Rusti Mawa; Yuliana, Yuliana; Suyuthie, Hijriyantomi (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
This research aims to see the effect of the work environment towards employee performance at Hotel Daima Padang. This research is measured through 2 variables, those are: (1) Work Environment (2) Employee Performance . The type of research is a quantitative descriptive with a causal approach using a simple linear regression test. The population of this research is employees of Hotel Daima Padang which amounted to 68 people. The sampling technique is simple random sampling, and the sample in this research amounted to 43 people. Primary data collection technique is done by using questionnaire with likert scale that have been tested the validity and reliability, secondary data is the employee performance taken at Daima Hotel Padang. The result of the research shows that: (1) The overall work environment is in bad category (53%), physical work environment is in bad category with percentage 58%, non physical work environment is in bad category 51% (2) Performance Employees are in adequate categories (42%), (3) work environment affects employee performance of 27.0%.Keywords: Work Environment, Employee Performance